1985
DOI: 10.2337/diacare.8.1.83
|View full text |Cite
|
Sign up to set email alerts
|

A Family Development Approach to Studying Factors in the Management and Control of Childhood Diabetes

Abstract: The study of family factors that relate to diabetes management and metabolic control is crucial because of the family's central role in this management. Four sequential phases of diabetes management are specified in this review: (1) the pre-onset stage; (2) the onset, crisis stage; (3) the accommodation stage; and (4) the stabilization stage. Each stage can be expected to influence the following stage. Thus, each is important to later management of the condition. No theory of family functioning provides a sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…Not only should families be aware of the client's condition, but they also should be allowed to ask their own questions. Several studies have shown that parental involvement impacts the metabolic control of diabetic adolescents (Newbrough, Simpkins, & Maurer, 1985;Lavalle, 2002;Skinner, John, & Hampson, 2000).…”
Section: Family Interventionmentioning
confidence: 97%
“…Not only should families be aware of the client's condition, but they also should be allowed to ask their own questions. Several studies have shown that parental involvement impacts the metabolic control of diabetic adolescents (Newbrough, Simpkins, & Maurer, 1985;Lavalle, 2002;Skinner, John, & Hampson, 2000).…”
Section: Family Interventionmentioning
confidence: 97%
“…IDDM as needed (3). Theoretically, family problems or marital distress could deleteriously affect metabolic control of the diabetic child by interfering with self-care or by causing stress-related physiological dysregulation (5).…”
mentioning
confidence: 99%
“…One aspect of cognitive dimension in the BPMHP is intelligence, which refers to knowledge. Based on the previous literature, knowledge necessary for performing DMTs is significantly related to better adherence (Newbrough, Simpkins, & Maurer, 1985). However, since the data set of the ABCs of Diabetes Study did not include data on knowledge, the effect of knowledge on adherence was not investigated in this study.…”
Section: Model Testingmentioning
confidence: 94%